SEDIAAN SALEP EKSTRAK DAUN KELOR (MORINGA OLEIFERA LAM) SEBAGAI PENYEMBUHAN LUKA BAKAR TOPIKAL PADA KELINCI (ORYCTOLAGUS CUNICULUS) - Wahyudi, Wahyudi; Agustina, Hanna (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2018)
Burns is a form of tissue damage caused by contact with a heat source such as fire, hot water, chemicals, electricity and radiation. Burns occur on the skin, mucous membranes, respiratory tract and gastrointestinal tract. Actions that can be performed on burns is to provide local treatment with the aim to get relief as quickly as possible. One of the traditional medicines used empirically society as burn treatment is by softening Moringa leaves Moringa leaves and placed on the affected part of the wound. This tudy aim to determine the effect of healing of burns using Moringa leaf extract ointment and to determine the concentration of Moringa leaf extract in the ointment preparation is most effective in the healing of burns. Experimental method. Result of this study show phytochemical screening results indicate the presence of alkaloids, flavonoids, saponins, tannins. observations of Moringa leaf extract ointment preparation during storage of 7 days showed that the formula has a good appearance, homogeneous, smell and color. Diameter burns decline, a group of rabbits treated with the ointment extract of the leaves of Moringa 6% that is 0.9 cm, a group of rabbits given ointment extract of the leaves of Moringa 8% ie 0.91 cm, a group of rabbits given ointment extract of Moringa leaves 10% that is 0.95 cm, BioplacentonÂ® namely the group given 0.89 cm, while the group of rabbits given distilled water of 0.77 cm. Conclusion of this study show that extracts leaves of Moringa had an effect in the healing of burns. Ointments Moringa leaf extract 10% of the most effective in the healing of burns and has a greater potential than the BioplacentonÂ®. Burn healing effect on the concentration of 8% and 6% more effective than the negative comparison.